ASEAN Security Analysis on Transnational Money Laundering Crimes: Formal Commitments and Practical Implementation Limitations - Qory Fizrianti Beru Sitepu; Mergera Akbar Sinergi Putra Agung (Faculty of Social and Political Sciences, Universitas Diponegoro, 2026)
Money laundering is a transnational crime that directly affects economic stability and regional security in Southeast Asia. Although ASEAN has made formal commitments and established various cooperative forums to enhance cross-border law enforcement capacity, the region continues to experience a rise in money laundering activities. This article examines how ASEAN's shared norms and collective identity influence the effectiveness of its efforts to combat money laundering. Drawing on the Constructivist Security Community framework, this study examines the interplay among the ASEAN Way, technocratic institutional culture, and voluntary compliance in shaping the region's anti–money laundering (AML) governance. The findings indicate that normative principles such as non-interference and consensus-building, while effective in preventing political conflict, simultaneously inhibit the development of binding legal and monitoring mechanisms. Moreover, ASEAN's elite-driven identity formation limits public engagement and collective accountability, resulting in a weak sense of ownership among member states. The study further finds that regional socialisation within ASEAN remains largely procedural—characterised by information sharing and symbolic cooperation rather than structural reform or enforcement. Consequently, ASEAN's anti–money laundering efforts reflect a pattern of symbolic compliance, where formal commitments coexist with limited domestic transformation. The article concludes that for ASEAN to address money laundering effectively as a regional security issue, its cooperative framework must evolve from consensus-based coordination toward normative and institutional integration.